A Contextualist Theory of Epistemic Justification - Annis, David B.; Salama, Mohamed Sayed (Nama Journal of Islamic Sciences and Humanities, 2023)
This article is a translation of "Contextual Theory of Cognitive Justification" by David B. Ennis. The research relied on a set of questions: 1) Can we learn anything about the issues of the outside world? 2) What guarantees us that the Earth did not come into existence only five minutes ago, but that it was completely created and deposited in it our false memories and beliefs that were placed in our brains that point to an imaginary ancient existence and fictitious ancient events? 3) If the brain is the center for receiving and processing sensations, what guarantees me that I am not just a brain in a container with a nutrient solution connected to an advanced computer to make my sensory perceptions in a virtual world in which I have a virtual body to deal with virtual people? These questions seem funny to any normal people. However, philosophers spare no effort in discussing and answering these questions.